What You See Is Not What You Get: Germ Cell Tumor Mimicking Disseminated Coccidioidomycosis - Haidar Hajeh MD; Hazem Aboaid MD; Kasey Fox DO; Everardo Cobos MD; Arash Heidari MD (Journal of Investigative Medicine High Impact Case Reports, 2023)
We present the case of a 30-year-old man with no prior medical history who presented to the hospital with a myriad of symptoms such as shortness of breath, generalized weakness, lower limb weakness, and urinary retention. He was recently diagnosed with “disseminated coccidioidomycosis” by an outside provider on an outpatient basis and started on fluconazole orally. However, due to a lack of improvement and significant symptoms, he was sent to the hospital to initiate liposomal amphotericin B treatment. After a comprehensive workup, an alternative diagnosis was suspected and eventually confirmed as metastatic germ cell carcinoma. Due to the vast dissemination and his poor functional status despite chemotherapy initiation, the patient elected for palliative care and expired shortly after at hospice. This case demonstrates the similarity of clinical findings between disseminated infections and malignancies.